Designing Animation Videos of Narrative Texts as Supplementary Reading Material - Meysithah Risky Dwiyani; Dwi Riyanti; Yanti Sri Rezeki (JELITA, 2024)
This study aimed to design and develop animation videos of narrative texts as supplementary material for the tenth-grade students of SMA N 9 Pontianak. Narrative texts are commonly extensive, which causes students to experience boredom and struggle while learning materials. This study emphasizes the needs of students who lack interest when reading narrative texts in English. Students require a tool that will assist them in understanding the narrative texts. This issue may be solved through the development of an animated video. However, the study only focused on the design and development of the animation video. This development research involved four phases: identifying needs, exploring needs, contextual realization, and production of materials. The subject of this study is the tenth-grade students of SMA N 9 Pontianak and the English Teacher as the evaluator. Three folklores of West Kalimantan have been developed into animated videos in this study, such as Bujang Nadi and Dare Nandung, The Crying Stone, and The Greedy Fisherman. The final product of this research was conceptualized for a group discussion, allowing students to participate actively in class activities. The findings revealed that the developed animation videos of narrative texts meet 90 percent criteria for supplementary reading material by the evaluator. Considering that the video is available on YouTube, it can be utilized in various educational settings as it covers the topic.